A case-control study of the effect of environmental sanitation on diarrhoea morbidity in Malawi. Issue 1 (March 1988) - Young, B; Briscoe, J
Abstract : A case-control design has been applied in the evaluation of improved environmental sanitation on diarrhoeal diseases in rural Malawi. The study demonstrates the feasibility of using such an approach to evaluate two levels of water supply and sanitation service quickly and at moderate cost. Sample sizes would need to be increased substantially to evaluate multiple levels of service or to investigate interactions between water supply and sanitation. The results indicate that children living in families who use good quality water supplies and latrines experience 20% less diarrhoea as reported to the health clinics during the warm, rainy season.